Sign and Its Significance in John's Gospel - Sihombing, Warseto Freddy; Tarigan, Iwan Setiawan (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2022)
John uses the term 'sign' in his Gospel to describe particular miracles that Jesus performs in His ministry as evidence of His divinity and sign posts to receive eternal life from God. By using an historically and theologically oriented hermeneutical method as a part of qualitative research, this article provides an interpretation of the seven signs in Gospel of John as authentic evidence of the main work of Jesus during His ministry on earth: namely, the revelation of Jesus divinity and consequent demands on people's lives, like responding to his claim as Savior. John deliberately chose the seven signs or miracles that Jesus performed. The significance of those signs reveals the glory of God within Jesus to a sinful world, so that those who see and know them will believe in Jesus Christ and receive the eternal life.